Trends of Marketing Management in Tourist Attractions - Shukla, Ajit Kumar (Indian Journal of Marketing, 2009)
Tourism has an international market, but marketing strategies need to be build up from the basic marketing inputs used in domestic tourism. Cultural differences (language and social usages), political differences (Income and its distribution and currency regulation), and geographical differences (topography and demography) are of supreme importance in the tourism and travel market. These environmental influences and their relationship to parallel influences in a particular region facilitate relocation of promising tourist markets. Marketing strategy inputs need to be adjusted to foreign markets. The tourist products (attractions) require simplification and adjustment to local differences in taste, price and quality levels. The long distance to an overseas market requires a concern with transportation and distribution; Differences in wholesaling and retailing require the use of different marketing channels. Prices must reflect the additional Costs of transportation, customers and other controls. Promotion needs adjustment to variation in travel media, availability of sales personnel and other promotional inputs. As the level of international tourism increases, the entire organization is directed towards the tourist and travel market.